Human Properdin Modulates Macrophage: Mycobacterium bovis BCG Interaction via Thrombospondin Repeats 4 and 5 - Al-Mozaini, Maha Ahmed; Tsolaki, Anthony G.; Abdul-Aziz, Munirah; Abozaid, Suhair M.; Al-Ahdal, Mohammed N.; Pathan, Ansar A.; Murugaiah, Valarmathy; Makarov, Evgeny M.; Kaur, Anuvinder; Sim, Robert B.; Kishore, Uday; Kouser, Lubna (Frontiers in Immunology, 2018)
Mycobacterium tuberculosis can proficiently enter phagocytes and diminish complement activation on its cell surface. Within phagocytes, the mycobacterium can suppress macrophage apoptosis and survive the intracellular environment. Complement regulatory proteins such as factor H may facilitate pathogen-macrophage interactions during tuberculosis infection. In this study, we show that M. bovis BCG binds properdin, an up-regulator of the complement alternative pathway. TSR4+5, a recombinant form of thrombospondin repeats 4 and 5 of human properdin expressed in tandem, which is an inhibitor of the alternative pathway, was also able to bind M. bovis BCG. Properdin and TSR4+5 were found to inhibit uptake of M. bovis BCG by THP-1 macrophage cells in a dose-dependent manner. Quantitative real-time PCR assays using transcripts from the THP-1 cells revealed elevated pro-inflammatory responses (TNF-α, IL-1β and IL-6) in the presence of properdin and TSR4+5, which gradually decreased over 6 hours. Correspondingly, anti-inflammatory responses (IL-10, TGF-β and IL-12) showed suppressed levels of expression in the presence of properdin, which gradually increased over 6 hours. Multiplex cytokine array analysis further revealed that properdin and TSR4+5 significantly enhanced the pro-inflammatory response (TNF-α, IL-1β and IL-1α) at 24 hours, which declined at 48 hours, whereas the anti-inflammatory response (IL-10 and IL-12) was suppressed. Our results suggest that properdin may interfere with mycobacterial entry into macrophages involving TSR4 and TSR5, particularly during the initial stages of infection, thus affecting the extracellular survival of the pathogen. This study offers novel insights into non-complement related functions of properdin, which may be independent of other complement proteins during host-pathogen interactions in tuberculosis. Thus, human properdin modulates macrophage-M. bovis BCG interaction via TSR4+5. Properdin residing in the granules of neutrophils is secreted upon stimulation and may also be produced by other cell types such as monocytes, bone marrow progenitor cell lines and T cells. The local production of properdin may be crucial for recruitment at sites of infection and in the control of M. tuberculosis infection.